2015
DOI: 10.23986/afsci.52313
|View full text |Cite
|
Sign up to set email alerts
|

Fungal species and multiple mycotoxin contamination of cultivated forage crops

Abstract: The quality of grass samples used for animal feed by combining mycotoxin measures and mycological determination of mycobiota were explored. The samples of the plant material were collected in 2014 in two stages: before the first mowing (May–June) and before the second one (July–August) from the fields of stock-farms located in northwestern part of the Russia. All samples were divided into three types: grasses, mixture of different grasses and clover, alfalfa mixed with timothy. The occurrence of aflatoxin B1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
1
20
0
4
Order By: Relevance
“…The representative of this genus A. alternata had a prevalence of 20.81% in pollen samples, which was by 10.63% higher than in the spring samples. Alternaria alternata, one of the most commonly encountered in the Alternaria genus, is the one which most abundantly produces mycotoxin alternariol (Kononenko et al, 2015). In 2011, Kačaniova found that Alternaria sp., Mycelia sterilia and Aspergillus candidus are often found in honey, with an occurrence of 1.0 × 10 2 CFU/g −1 to 4.50 × 10 3 CFU/g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The representative of this genus A. alternata had a prevalence of 20.81% in pollen samples, which was by 10.63% higher than in the spring samples. Alternaria alternata, one of the most commonly encountered in the Alternaria genus, is the one which most abundantly produces mycotoxin alternariol (Kononenko et al, 2015). In 2011, Kačaniova found that Alternaria sp., Mycelia sterilia and Aspergillus candidus are often found in honey, with an occurrence of 1.0 × 10 2 CFU/g −1 to 4.50 × 10 3 CFU/g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Seeds with high initial vigour, foliage growth and good germination provide more biomass and also provides edge to weed competition in their natural growth conditions (Maity et al, 2016). One of the main impediments towards the availability of good quality seeds is seed borne pathogens (Naqvi et al, 2013;Kononenko et al, 2015), which account for annual economic loss of more than US $130 million in Afro-Asian countries (Yago et al, 2011). They reduce seed viability by associating with the seed either externally or internally and may cause seed abortion, seed rot, seed necrosis and reduction or elimination of germination capacity as well as seedling damage.…”
Section: Introductionmentioning
confidence: 99%
“…For the last few decades, use of agrochemicals for seed treatment has certainly decreased the incidence of seed mycoflora, but at the same time has contributed to the development of resistant pathogens (Elad et al, 1992). Moreover, such chemicals can be lethal to beneficial microorganisms in the rhizosphere and useful soil insects, and they may also enter the food chain and accumulate in undesirable levels (Kononenko et al, 2015). With the emergence and proliferation of microbes resistant to fungicides and the burgeoning health care costs, many researchers have been tried to develop new and effective antimicrobial reagents that do not stimulate resistance and are less expensive.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of mycotoxin contamination of many food commodities [7] [8] [9] including seeds and legumes [10] [11] [12], which soya bean belongs to. These mycotoxins are known to have very adverse health effects including carcinogenic, immunosuppressive, mutagenic and cytotoxic effects [4] [13].…”
Section: Introductionmentioning
confidence: 99%